Homogenate Extraction of Dihydroartemisinin from Artemisia Hedinii and Its Antifungal Activity. (23rd January 2021) - You, Cong; Yu, Jun; Qin, Guangjiong; Yang, JinPeng; Yang, Chunlei; Hu, Guoyuan
Abstract: Background: Artemisia hedinii is a well-known traditional Chinese medicine. It can be used to extract dihydroartemisinin (DHA). Objective: The purpose of this study was to explore the optimal conditions for the homogenate extraction of DHA from A. hedinii and the antifungal activity of DHA. Methods: In this study, single-factor experiments and the response surface method were used to determine the optimal extraction conditions of crude extract and DHA. The method of spore germination was used to study the antifungal activity of DHA on Alternaria alternata . Results: The optimal conditions were found as follows: ratio of liquid to material 22 mL/g; extraction time 60 s; and soaking time 34 min. Under these conditions, extraction yield of DHA was (1.76 ± 0.04%). When the concentrations of crude extract were 0.5 and 8 mg/mL, the spore germination inhibition rates of A. alternata were (17.00 ± 2.05%) and (92.56 ± 2.01%), which were 3.34 and 1.15 times that of the DHA standard, respectively. Conclusions: Homogenate extraction technology is a fast and efficient method for extracting DHA from A. hedinii . The crude extract has significant antifungal activity against A. alternata and is inexpensive, providing possible DHA usage in the prevention and treatment of plant pathogenic fungi. Highlights: The optimum conditions of the extraction of DHA from A. hedinii by homogenate extraction were obtained. DHA has antifungal activity against A. alternata . Compared with pure DHA, the crude extract has stronger antifungal activity against A. alternata.